O mito de Ulisses como metáfora do processo de individuação masculino no modelo junguiano - Said, Leticia Goncalves (2019)
Homer’s Odyssey tells the story of Odysseus’ troublesome journey back to Ithaca, following the end of the Trojan War. This epic poem, written roughly 2700 years ago, continues to this day to be an extremely influential work, as a synonymous for a long and dangerous hero’s journey, with several of its passages, such as the Cyclops, the Trojan Horse and Penelope’s shroud now belonging to Western mythical culture. According to analytical psychology, myths contain a archetypical symbols, namely, they contain primordial symbols common to all humanity. This thesis’ goal is to suggest that Homer’s work is a metaphor of Jung’s individuation process, drawing comparisons between Odysseus’ myth and the different stages of this process. In order to achieve this, a symbolic reading of the poem was made, using Jung and other jungian authors as theoretical background. It is established that the beginning of the journey – when Odysseus is cut off from the rest of the Achean heroes – marks the beginning of the individuation process; his relationships with the opposite sex represent the confrontation with the anima; the help he receives from Hermes and his descent to Hades signify the encounter with the Self; Odysseus’ men, his feud with Poseidon and Polyphemus correspond to the shadow’s integration; and when he washed up on the Phaecian cost naked, alone and without any riches, it represents the breakdown of the persona. From these parallels, it is argued that the hero’s extensive individuation process is a result of his own choices and a need to integrate his inferior psychological function, the feeling